Rural Cinema Exhibition and Audiences in a Global Context (Global Cinema, 2018)
Although it has only been in the last decade that the planet's population balance tipped from a predominantly rural makeup towards an urban one, the field of cinema history has demonstrated a disproportionate skew toward the urban. Within audience studies, however, an increasing number of scholars are turning their attention away from the bright lights of the urban, and towards the less well-lit and infinitely more variegated history of rural cinema-going. Rural Cinema Exhibition and Audiences in A Global Context is the first volume to consider rural cinema-going from a global perspective. It aims to provide a rich and wide-ranging introduction to this growing field, and to further develop some of its key questions. It brings together eighteen international scholars or teams, all representatives of a dynamic, new field. Moving beyond a Western focus is essential for thinking through questions of rural exhibition, distribution and cinema experience, since over the relatively short history of cinema it is the rural that has dominated cinema-goers' lives in much of the developing world. To this end, the volume also innovates by bringing discussions of North American and European ruralities into dialogue with contributions on Kenya, Brazil, China, Thailand, South Africa and Australia.